Data Management in Grid and Peer-to-Peer Systems 4th International Conference, Globe 2011, Toulouse, France, September 1-2, 2011, Proceedings - Hameurlain, Abdelkader; Tjoa, A Min (Information Systems and Applications, incl. Internet/Web, and HCI, 2011)
This book constitutes the refereed proceedings of the 4th International Conference on Data Management in Grid and Peer-to-Peer Systems, Globe 2011, held in Toulouse, France, in September 2011 in conjunction with DEXA 2011. The 12 revised full papers presented were carefully reviewed and selected from 18 submissions. The papers are organized in topical sections on data storage and replication, semantics for P2P systems and performance evaluation, resource discovery and routing in mobile P2P networks, and data stream systems and large-scale distributed applications.